Metabolic Syndrome in Obese and Non-Obese Individuals Presented at A Tertiary Care Hospital of Hyderabad, Pakistan : Metabolic Syndrome in Obese and Non-Obese Individuals - Tariq, Javeria; Humaira, Mona; Ahmed, Atif; Memon, Abeer; Memon, Naila; Shah, Madiha (Pakistan Journal of Health Sciences, 2024)
Metabolic Syndrome (MetS) has proved to be of enormous negative impact on health of humans, even in case of non-obese people. Objective: To determine the frequency of metabolic syndrome in obese and non-obese individuals at Liaquat University Hospital Hyderabad/Jamshoro. Methods: This Cross sectional comparative study was conducted on 122 persons, 61 obese and 61 non-obese persons, chosen through Non probability consecutive sampling technique. Patients of either gender, aged between 30 to 60 years, visited the OPD or hospitalized were selected. The patients with acute or chronic Ischemic heart disease or stroke, liver, lung or kidney or thyroid diseases or suffering from malignancy along with Pregnant ladies and lactating mothers were excluded. MetS was diagnosed via IDF and AHA classification. Results: Metabolic Syndrome (MetS) was significantly more prevalent in obese individuals (70.5%) than in non-obese individuals (19.7%) (p = 0.001). Obese participants had a higher BMI (29.24 kg/m² versus 20.70 kg/m², p = 0.001), greater prevalence of dyslipidemia (63.9% versus 16.4%, p = 0.001), and uncontrolled diabetes (41.0% versus 13.1%, p = 0.001). Blood pressure was significantly elevated in the obese group, with mean systolic and diastolic pressures of 143.52 mmHg and 93.11 mmHg, respectively (p = 0.001). Conclusion: MetS was present in 45.1% of the participant and was found to be strongly consistent with obesity although it was also detected in noteworthy portion of non-obese persons.